2011
DOI: 10.1371/journal.pone.0020999
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence of Mycoplasma bovis Strain Hubei-1

Abstract: Infection by Mycoplasma bovis (M. bovis) can induce diseases, such as pneumonia and otitis media in young calves and mastitis and arthritis in older animals. Here, we report the finished and annotated genome sequence of M. bovis strain Hubei-1, a strain isolated in 2008 that caused calf pneumonia on a Chinese farm. The genome of M. bovis strain Hubei-1 contains a single circular chromosome of 953,114 bp with a 29.37% GC content. We identified 803 open reading frames (ORFs) that occupy 89.5% of the genome. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 56 publications
(51 reference statements)
2
68
0
Order By: Relevance
“…S1 in the supplemental material). The vestigial ICE harbored by M. agalactiae PG2, vICEA PG2 , appeared more similar to ICEM GM12 than to ICEA 5632 : the overall nucleotide identity was higher (Table 1), and vICEA PG2 displayed (14). For calculating the identity percentage, the IS elements were removed from ICEA 5632 -IV and ICEB PG45 -2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 in the supplemental material). The vestigial ICE harbored by M. agalactiae PG2, vICEA PG2 , appeared more similar to ICEM GM12 than to ICEA 5632 : the overall nucleotide identity was higher (Table 1), and vICEA PG2 displayed (14). For calculating the identity percentage, the IS elements were removed from ICEA 5632 -IV and ICEB PG45 -2.…”
Section: Resultsmentioning
confidence: 99%
“…As well, vICEB PG45 -1 of M. bovis PG45 had a higher overall nucleotide identity with ICEM GM12 than with ICEB PG45 -2 (Table 1) and also harbored CDSs found only in ICEs of the spiroplasma type (i.e., CDS3, CDS33, CDS18, and CDSZ). These characteristics are shared by the vICEs carried by the 2 recently sequenced genomes from M. bovis isolates from China, namely, those of strains Hubei (14) and HB0801 (15), both having a unique highly conserved vICE similar to vICEB-1 PG45 (97% global identity). Finally, sequence comparison showed that vICEA 5632 -IV and vICEA 5632 -V are of the spiroplasma type whereas the remote CDS1 and CDSE of both M. bovis Hubei and M. bovis HB0801 are of the hominis type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P48 is a membranous lipoprotein of slightly lower than 48kDa that is homologous to the family of the Macrophage Activator Lipoproteins (MALPs) and it is coded via a conserved sequences specific to the M. bovis species (Wawegama et al, 2014), so the sequence of M. bovis strain PG45 under accession number of CP002188 was selected (Wise et al, 2011) to compare with the strains detected in this study. The encoding gene sequence of lipoprotein P48 is recorded as accession numbers of DQ020481 and DQ020482 at Gene Bank (Lysnyansky et al, 2008) and it is known as one of the virulence factors of M. bovis species (Li et al, 2011). As the P48 gene is well conserved in all M. bovis strains, primers with high sensitivity and specificity were designed (Fu et al, 2014), and used for the amplification of P48 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma bovis Strain Hubei-1, sequence accession CP002513 [85] Mycoplasma fermentans Strain M64, sequence accession NC_014921 [86] Haloplasma contractile, sequence accession AFNU00000000 [87] Mycoplasma ovipneumoniae Strain SC01, sequence accession AFHO01000000 [88] Phylum Actinobacteria…”
Section: Tenericutesmentioning
confidence: 99%